OP11 Premature mortality in adult survivors of child abuse and neglect. (3rd September 2019) - Rogers, NT; Power, C; Pereira, SP
Abstract : Background: Child maltreatment (neglect and abuse) is not uncommon and has established associations with adverse socioeconomic and health outcomes; however there is sparse evidence on its relationship with premature mortality in adulthood. While different types of maltreatment co-occur, previous studies have examined types of maltreatment separately or as a combined score and there is little understanding of possible differential effects. Using a general population birth cohort, we aimed to establish whether different types of maltreatment were associated with risk of all-cause mortality in mid-adulthood. Methods: Using data from the 1958 British cohort (N=9311), we examined associations between child neglect (prospectively recorded at 7y and 11y) and physical, psychological, witnessing and sexual abuse (retrospectively recorded at 44/45y) with risk of all-cause mortality between 2002/3 (when participants were 44/45y) and December 2016. Death was ascertained through receipt of certificates from the NHS Central Register (n=296) and from information from relatives or close friends (n=16). Associations were examined for each type of maltreatment separately and also combined as a score, to assess cumulative burden, using Cox proportional hazard models with and without adjustment for gender, early-life covariates (e.g. childhood socioeconomic position) and for other maltreatment types to allow for co-occurrence. Results: Approximately 22% of participants reported at least one type of maltreatment in childhood and 3.4% had died between 2002/3 and 2016. Individuals identified with neglect (10.4% of the population), physical (6%) or sexual abuse (1.6%) were at increased risk for all-cause mortality during the follow-up period, independent of other types of maltreatments and childhood socioeconomic position: adjusted Hazard Ratios (HRs) were 1.43(95% CI:1.04, 1.95), 1.76(1.11, 2.80) and 3.07(1.77, 5.33) respectively. Childhood psychological and witnessing abuse were not associated with mortality after allowing for other factors. In general, risk of all-cause mortality increased with number of types of maltreatment, with HRs of 1.61(1.21, 2.14) and 3.43(2.28, 5.17) for a single and 3+ types of maltreatments respectively, compared to those with none. Conclusion: Adult survivors of child neglect, physical and sexual abuse are at increased risk of premature mortality in mid-adulthood. Findings suggest that periodic health assessments for survivors of specific types of child maltreatment over the life-course may help eradicate differences in premature mortality. Child abuse was reported retrospectively in adulthood, although child neglect and potential confounding factors were ascertained prospectively.